FIELD MODELING OF THE SYSTEM-FORMING CONCEPT «VERBRECHEN» AS A REFLECTION OF THE STRUCTURE OF MASS CONSCIOUSNESS OF MODERN SOCIETY (BASED ON GERMAN POLICE NOVEL) - A. V. Ralovets (Гуманитарные и юридические исследования)
This article studies the detective text as an important component of mass literature, reflecting stable models of mass consciousness. The article considers the characteristic features of mass culture society, which form the image of modern recipient and influence the character of the texts of modern culture. The detective is studied as a text space that implements the message of mass culture society, with an emphasis on German detective literature and its specific features. The scientific novelty of this work lies in the field modeling of the basic concept for a police detective «VERBRECHEN» («CRIME») taking into account the factors of influence on the recipient, in identifying the linguistic and cognitive features of its representation on the material of the popular German detective «Die Lebenden und die Toten» (2014), written by Nele Neuhaus. Illustrative examples show that the nuclear zone of the concept «VERBRECHEN» consists of semantically related categories of the act itself: Kapitalverbrechen, Mord, Mordfall, Straftat, Totschlag, Tötungsdelikt, Tötung, menschliche Verfehlung, supplemented by the criminal designations: Verbrecher, Mörder, Täter. The peripheral layers of this concept are implemented in such local concepts as «Schuld» (guilt), «Eitelkeit» (vanity), «Unsittlichkeit» (immorality), «Rache» (revenge), the emotive components of the concept «VERBRECHEN» «Angst» (fear), «Zorn» (anger), «Schmerz» (pain). The concept «ERMITTLUNG» (investigation) is connected with the backbone concept «VERBRECHEN» in a meaningful and procedural way, the semantic content of which is characterized in the author’s evaluative understanding both different aspects of the crime and the personality of the criminal.